World Econonomic and Financial Surveys, 1988 : Staff Studies for World Economic Outlook. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1988)
This paper examines the World Economic Outlook forecasting record for the principal performance indicators for the major industrial countries and corresponding aggregates and for groups of non-oil developing countries. Several criteria were used in evaluating the forecasts: the computation and evaluation of various summary statistics of forecast accuracy, bias, and efficiency; comparisons with alternative forecasts-naive forecasts and forecasts produced by the Organization for Economic Cooperation and Development (OECD) and by national forecasting agencies; the examination of turning-point errors and forecast performance in defined episodes; and, finally, some attempt to explain forecast error in terms of unanticipated developments in policy variables and oil prices. In judging the forecast performance of the World Economic Outlook, a number of points must be kept in mind. Most important, it has to be recognized that the period since the inception of the World Economic Outlook as a regular forecasting exercise has been extraordinarily rich in economic upheavals, which have made the odds against accurate forecasting formidable.